IMPLEMENTASI PROGRAM PEMBERIAN ASI EKSKLUSIF DI UPTD PUSKESMAS GADUNG KABUPATEN BUOL - Emitriana Emitriana; I Kadek Wartana (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2020)
Exclusive breastfeeding is still very low, that is, it has not reached the 80% standard with the number of babies 0-6 months in the Gadung Health Center working area. Given the importance of exclusive breastfeeding in improving the health status of infants and the low coverage of exclusive breastfeeding, which is still far from expectations. This type of research is descriptive research. Research variables include input, process, output in the exclusive breastfeeding program at Puskesmas Gadung, Buol Regency. Data were collected by interview method accompanied by observation. Respondents in this study were 9 health workers who are directly related to the exclusive breastfeeding program. The results showed that there are inputs in the implementation of the exclusive breastfeeding program at Gadung Health Center, namely health personnel, implementation rooms, media and supporting equipment and targets served in the exclusive breastfeeding program, while the operational costs of the exclusive breastfeeding program do not exist The process of implementing the exclusive breastfeeding program at Gadung Health Center is counseling, counseling and IMD. The output in the implementation of the exclusive breastfeeding program at Gadung Health Center was 30.2%, not yet reaching the standard requirement of 80%. It is recommended that the Gadung Health Center be able to improve the performance of employees especially those who handle the Exclusive Breastfeeding Program so that program achievements are in line with the minimum service standards.